Reaching Unserved Communities in Africa with Basic Services : Can Small-Scale Private Service Providers Save the Day? - Kariuki, Mukami; Schwartz, Jordan; Schur, Michael (World Bank, Washington, DC, 2012)
With urban and especially periurban populations set to grow at unprecedented rates in Africa, and service coverage continuing to lag, governments and donors have begun to recognize that small-scale providers have an increasingly critical role to play. They have also begun to focus on the importance of creating an environment that enables these providers to supply good quality service. Most African countries face big deficits in infrastructure, and their efforts to scale up the services of small-scale service providers may be impeded by lack of capacity or resources or even by collusion and rent seeking by larger, formal service providers. Improving or extending the services of small scale service providers must therefore be part of-not a substitute for-reform of the infrastructure sector.